Correlation between family support and the level of compliance with diabetes diet control: A cross-sectional study - Aprita, Aprita (Science Center Group, 2024)
Background: Effective diabetes management requires consistent dietary adherence to achieve optimal glycemic control and prevent long-term complications. Family support plays a crucial role in influencing dietary behaviors among patients with diabetes, particularly in community settings where self-management is largely carried out at home. Objective: This study aimed to examine the relationship between family support and dietary compliance among patients with diabetes in a community setting. Methods: A quantitative cross-sectional study was conducted involving 200 patients with diabetes recruited from community health centers. Participants were selected using a purposive sampling technique. Data were collected using structured questionnaires that included demographic characteristics and standardized instruments to measure family support and dietary adherence. Data analysis was performed using Pearson’s correlation test to assess the association between family support and dietary compliance. Results: The analysis revealed a statistically significant positive correlation between family support and dietary compliance (r = 0.58; p = 0.002). Patients who reported higher levels of family support demonstrated better adherence to recommended dietary regimens compared to those with lower levels of support. Conclusion: Family support is significantly associated with dietary compliance among patients with diabetes. Strengthening family involvement through community-based and family-centered nursing interventions may enhance dietary adherence and contribute to improved diabetes management outcomes.